A Comparative Study of the Actual and Ideal State of Social Welfare between Rural and Urban Dwellers (Case Study of Azna City) - Kobra Shahrisvand; Hosein Asadi Davodabadi; Omid Aliahmadi; Roshanaei Ali (توسعه اجتماعی, 2024)
The purpose of this research is to study the real and ideal social well-being of rural and urban residents of Azna city, which was conducted by survey method. The statistical population of this research includes all the citizens of Azna city, which according to the census of 2015 was equal to 71586 people. The sample size was 384 people who were selected by stratified random sampling method. The results of the research show that the real well-being of the residents of urban and rural areas is different. In this regard, age groups (Beta=0.387) are higher for real well-being compared to its value for ideal well-being (Beta=0.431). Also, this result for marital status is equal to (Beta=0.325) and (Beta=0.389); for welfare policies equal to (Beta=0.373) and (Beta=0.373); for cultural and media consumption equal to (Beta=0.404) and (Beta=0.539); For religiosity it is equal to (Beta=0.243) and (Beta=0.393). It is concluded that the real and ideal well-being of urban and rural residents are different. In this sense, the real and ideal well-being for rural residents is lower than the level of well-being in urban environments in both the real and ideal dimensions; this situation can be caused by the low level of expectations of villagers compared to urban residents.